Co‐occurrence of BAP1 and SF3B1 mutations in uveal melanoma induces cellular senescence - Le Yu; Dan Zhou; Guiming Zhang; Zhonglu Ren; Xin Luo; Peng Liu; Steven W. Plouffe; Zhipeng Meng; Toshiro Moroishi; Yilei Li; Yiyue Zhang; Joan Heller Brown; et al. (Molecular Oncology, 2022)
Uveal melanoma (UM) is the most common intraocular tumor in adults. Recurrent mutations in BRCA1‐associated protein 1 (BAP1) and splicing factor 3B subunit 1 (SF3B1) display a mutually exclusive pattern in UM, but the underlying mechanism is unknown. We show that combined BAP1 deficiency and SF3B1 hotspot mutation lead to senescence and growth arrest in human UM cells. Although p53 protein expression is induced, deletion of TP53 (encoding p53) only modestly rescues the observed senescent phenotype. UM cells with BAP1 loss or SF3B1 mutation are more sensitive to chemotherapeutic drugs compared with their isogenic parental cells. Transcriptome analysis shows that DNA‐repair genes are downregulated upon co‐occurrence of BAP1 deletion and SF3B1 mutation, thus leading to impaired DNA damage response and the induction of senescence. The co‐occurrence of these two mutations reduces invasion of UM cells in zebrafish xenograft models and suppresses growth of melanoma xenografts in nude mice. Our findings provide a mechanistic explanation for the mutual exclusivity of BAP1 and SF3B1 mutations in human UM.